2019
DOI: 10.1016/j.cognition.2019.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Memory enhancements from active control of learning emerge across development

Abstract: This paper investigates whether active control of study leads to enhanced learning in 5-to 10-year-olds. Children played a simple memory game. In Experiments 1 and 2, the goal was to remember as many as possible from 64 objects. In Experiment 3, the goal was to learn the French names for the same objects. For half of the materials presented, participants could decide the order and pacing of study (Active condition). For the other half, they passively observed the study decisions of a previous participant (Yoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 50 publications
9
47
0
Order By: Relevance
“…The observed greater effectiveness of GLSs during late-elementary/early-secondary school dovetails with the observation that it is during these grades (i.e., around age 10) that one can observe the emergence of abstract self-reflection in children, which enables an efficient use of knowledge-based learning strategies (e.g., Hasselhorn 1995). Findings are also in line with a recent study that showed that the advantage from giving learners active control over their learning increases across middle childhood (Ruggeri et al 2019). What this line of research cannot explain straightforwardly, however, are the differences in developmental trajectories between strategies.…”
Section: Discussionsupporting
confidence: 90%
“…The observed greater effectiveness of GLSs during late-elementary/early-secondary school dovetails with the observation that it is during these grades (i.e., around age 10) that one can observe the emergence of abstract self-reflection in children, which enables an efficient use of knowledge-based learning strategies (e.g., Hasselhorn 1995). Findings are also in line with a recent study that showed that the advantage from giving learners active control over their learning increases across middle childhood (Ruggeri et al 2019). What this line of research cannot explain straightforwardly, however, are the differences in developmental trajectories between strategies.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, though few studies have examined causal learning in adolescence, our results demonstrate that causal learning and decision-making continue to change during this period. This finding contributes to the growing body of literature examining how the ability to effectively support one's own learning changes over developmental time (Kachergis, Rhodes, & Gureckis, 2017;Ruggeri, Markant, Gureckis, Bretzke, & Xu, 2019). Future work probing the cognitive mechanisms that drive these changes will inform our understanding of how children and adolescents shape their own learning opportunities as they interact with their environments with increasing independence.…”
Section: Discussionmentioning
confidence: 63%
“…The current study aims to advance this debate by investigating the cognitive basis of self-directed learning (T. M. Gureckis & Markant, 2012;Markant et al, 2016). Whereas recent studies have demonstrated that learner control enhances elemental encoding of information directly experienced during study Murty, DuBrow, & Davachi, 2015;A. Ruggeri, Markant, Gureckis, & Xu, 2019;Voss et al, 2011), less is known about how active control impacts integrative encoding, through which experienced information is combined into generalizable knowledge during study.…”
Section: Discussionmentioning
confidence: 99%